Extraction of gallium from Bayer liquor using extractant produced from cashew nutshell liquid - Hoang, A.; Nguyen, H.; Bui, N.; Vu, H.; Vo, T.; Nguyen, Thanh Vinh; Phan, Chi (Elsevier, 2015)
Oximes of alkyl salicylaldehydes were synthesized from cardanol extracted from cashew nutshell liquid with SnCl4 as a catalyst. Molecular structures, physical and chemical properties of these oximes were investigated by spectroscopic data. These oximes were used as gallium extractant from a concentrated Bayer liquor of Alumina Tanrai (Vietnam). Results indicated that about 80% of gallium was recovered. This study opens up new opportunities to employ an environmentally friendly extractant for recovery of precious metals from industrial waste.